THE INFLUENCE OF PLASMA ENVIRONMENT INTERACTION ON SATELLITE LAPAN-TUBSAT ANOMALY - - NIM: 20315004 , NEFLIA
An anomaly is a condition that deviates from normal condotions or from expected conditions. Anomalies in spacecraft may harm the electronic health of the spacecraft, affect the functioning of the instrument, and may also cause satellite missions to fail. The anomalies that occur on the satellite are closely related to the satellite's interactions with the environment in which they are placed. In this research we will analyze the variation of energetic particle in the range of 3 days before and one day after the occurrence of anomaly on LAPANTUBSAT satellite in order to find the characteristic of plasma environment at the time of the anomaly. Position, local satellite time and possible disruption experienced by the LAPAN-TUBSAT are also measured. In achieving this goal we used electron data with energy> 30 keV, >100 keV, >300 keV, proton flux with energy 30-80 keV, 80-240 keV and 240-800 keV from NOAA 15 satellite, satellite orbit data and LAPAN-TUBSAT satellite anomaly information and the EQUIPOT program to determine the satellite potential. The results showed that most of the anomaly occurred in the distribution of protons and electrons, which south pole have 7 cases, north pole have 10 cases and SAA have 48 cases of anomaly, although there were 17 cases of anomalies that were not in the distribution of protons and electrons. The local satellite time indicates that the most of anomalies occur at 8:00 LT (23 cases) and 20.00 LT (24 cases). The electron flux varies from 10 to 105 electrons/cm2/sec/ster while the proton flux varies from 0 to 104 proton/cm2/sec/ster. There are no specific characteristics of particle flux. It indicates that the anomaly occurring on LAPAN-TUBSAT satellite not only occurs spontaneously when the satellite interacts with the particles but can also be the accumulation of charging that occurs on the satellite. In addition, during the reported anomaly, satellite potential measured by using EQUIPOT is negative, ranging from -43.90 V to -0.10 V, which means that the interaction between the satellite surface and the particles causes more electrons accumulation on the satellite surface than with ions in satellite material. The charging on LAPAN-TUBSAT satellite has not been categorized as endangering the satellite despite the increase in current on the satellite system.